PENEGAKAN HUKUM TERHADAP ILLEGAL LOGGING DI INDONESIA DITINJAU DARI PERSPEKTIF HUKUM PIDANA - Yeyen Andrizal (SOL JUSTICIA, 2019)
As we all know that in the current era of development, each country is demanded to be able to increase development in order to catch up or equal the countries that are considered established in order to sustain international stability. The development is specifically directed towards realizing just and prosperous community welfare in each country, including Indonesia, with regard to all aspects including the environmental aspects, as explained in article 33 paragraph 3 of the 1945 Constitution as a constitutional foundation, namely: "... The earth, water and natural resources contained therein are controlled by the State and used for the greatest prosperity of the people ..." This important environmental aspect is based on the preservation and protection of natural resources as a common right to be enjoyed and must be safeguarded in order to continue to provide benefits in their daily lives. Apart from that, the forestry sector as one part of the environment, is a gift from God Almighty and is one of the natural resources that is very important for humans. The research method carried out is a normative research method so that the literature used comes from literature, books and legal dictionaries. The results of this study are criminal law enforcement against illegal logging, regulated in criminal provisions in Article 50 and criminal penalties in Article 78 of Law Number 41 of 1999 concerning Forestry, but regarding the provisions of the procedural law concerning proof in criminal acts Illegal Logging at trial is based on the Criminal Procedure Code (KUHAP) Chapter XVI articles 183 and 184